Statistics in the second level curriculum - Stuart, Michael (Statistical and Social Inquiry Society of Ireland, 1985)
The existence of the Curriculum and Examinations Board, started in January 1984 by the Minister for Education, provides an opportunity for reviewing the position of statistics in the second level curriculum and making appropriate proposals for change. The terms of reference of the board call for the investigation of (among other topics) (l) assessment of the junior level, (n) the Leaving Certificate as a measure of general education, (in) alternative senior cycle programmes, and call for wide consultation on these and other topics. The Board has already published consultative documents, (1), (2), and has set up a number of committees and working parties with members largely drawn from outside the Board itself. It is clear from its work to date that the Board is taking a very broad view.
Read before the Society, 28th May, 1985
Keywords: Leaving Certificate curriculum; Statistics; 314.15